PENGEMBANGAN E-BOOK INTERAKTIF PADA MATA PELAJARAN BAHASA INDONESIA MATERI ```'AYO KERJA SAMA” UNTUK SISWA KELAS V SD NEGERI 3 ANDOWIA - Muhammad Sahir; Alfiah Fajriani; Zila Razilu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning Indonesian language in elementary schools still requires instructional media that can improve students’ engagement and understanding in the learning process. Th is study aimed to develop an interactive e-book as a learning medium for Indonesian language subjects and to determine its feasibility, practicality, and effectiveness in supporting learning activities. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included teachers and 26 fifth-grade students of SD Negeri 3 Andowia, North Konawe Regency. Data were collected through expert validation questionnaires, student response questionnaires, observations, and learning outcome tests. Data analysis used qualitative and quantitative approaches. The results showed that the developed interactive e-book was categorized as highly feasible, with a media expert validation score of 92% and a material expert validation score of 96%. In addition, student responses reached 90%, indicating that the learning media was practical and easy to use in the learning process. The effectiveness of the e-book was also reflected in the improvement of students’ learning outcomes after using the media during learning activities. Therefore, the developed interactive e-book was declared valid, practical, and effective as a learning medium for Indonesian language subjects in elementary school. This product is expected to become an innovative digital learning medium to improve the quality of learning and students’ learning interest in elementary schools.